Vegetarian diet as a risk factor for tuberculosis in immigrant south London Asians. Issue 2 (February 1995) - Strachan, D P; Powell, K J; Thaker, A; Millard, F J; Maxwell, J D
Abstract : BACKGROUND--In a previous retrospective study of tuberculosis in south London among Asian immigrants from the Indian subcontinent Hindu Asians were found to have a significantly increased risk for tuberculosis compared with Muslims. This finding has been further investigated by examining the role of socioeconomic and lifestyle variables, including diet, as risk factors for tuberculosis in Asian immigrants from the Indian subcontinent resident in south London. METHODS--Using a case-control study technique Asian immigrants from the Indian subcontinent diagnosed with tuberculosis during the past 10 years and two Asian control groups (community and outpatient clinic controls) from the Indian subcontinent were investigated. Cases and community controls were approached by letter. A structured questionnaire concerning a range of demographic, migration, socioeconomic, dietary, and health topics was administered by a single trained interviewer to subjects (56 cases and 100 controls) who agreed to participate. RESULTS--The results confirmed earlier findings that Hindu Asians had an increased risk of tuberculosis compared with Muslims. However, further analysis revealed that religion had no independent influence after adjustment for vegetarianism (common among Hindu Asians). Unadjusted odds ratios for tuberculosis among vegetarians were 2.7 (95% CI 1.1 to 6.4) using community controls, and 4.3 (95% CI 1.8 to 10.4) using clinic controls. There was a trend of increasing risk of tuberculosis with decreasing frequency of meat or fish consumption. Lactovegetarians had an 8.5 fold risk (95% CI 1.6 to 45.4) compared with daily meat/fish eaters. Adjustment for a range of other socioeconomic, migration, and lifestyle variables made little difference to the relative risks derived using either community or clinic controls. CONCLUSIONS--These results indicate that a vegetarian diet is an independent risk factor for tuberculosis in immigrant Asians. The mechanism is unexplained. However, vitamin D deficiency, common among vegetarian Asians in south London, is known to affect immunological competence. Decreased immunocompetence associated with a vegetarian diet might result in increased mycobacterial reactivation among Asians from the Indian subcontinent.